Water- and Nitrogen-Use Efficiencies of Hemp (Cannabis sativa L.) Based on Whole-Canopy Measurements and Modeling - Tang, Kailei; Fracasso, Alessandra; Struik, Paul C.; Yin, Xinyou; Amaducci, Stefano (Frontiers in Plant Science, 2018)
Interest in hemp (Cannabis sativa L.) as a crop for the biobased economy is growing worldwide because hemp produces a high and valuable biomass while requiring low inputs. To understand the physiological basis of hemp’s resource-use efficiency, canopy gas exchange was assessed using a chamber technique on canopies exposed to a range of nitrogen (N) and water levels. Since canopy transpiration and carbon assimilation were very sensitive to variations in microclimate among canopy chambers, observations were adjusted for microclimatic differences using a physiological canopy model, with leaf-level parameters estimated for hemp from our previous study. Canopy photosynthetic water-use efficiency (PWUEc), defined as the ratio of gross canopy photosynthesis to canopy transpiration, ranged from 4.0 mmol CO2 (mol H2O)-1 to 7.5 mmol CO2 (mol H2O)-1. Canopy photosynthetic nitrogen-use efficiency (PNUEc), the ratio of the gross canopy photosynthesis to canopy leaf-N content, ranged from 0.3 mol CO2 d-1 (g N)-1 to 0.7 mol CO2 d-1 (g N)-1. The effect of N-input levels on PWUEc and PNUEc was largely determined by the N effect on canopy size or leaf area index (LAI), whereas the effect of water-input levels differed between short- and long-term stresses. The effect of short-term water stress was reflected by stomatal regulation. The long-term stress increased leaf senescence, decreased LAI but retained total canopy N content; however, the increased average leaf-N could not compensate for the lost LAI, leading to a decreased PNUEc. Although hemp is known as a resource-use efficient crop, its final biomass yield and nitrogen use efficiency may be restricted by water limitation during growth. Our results also suggest that crop models should take stress-induced senescence into account in addition to stomatal effects if crops experience a prolonged water stress during growth.